Pengembangan Permainan Scrabble Kimia sebagai Media Pembelajaran pada Materi Minyak Bumi Kelas XI SMA - Rahma Yuni Fadlah; Bayharti Bayharti (Universitas Negeri Padang, 2019)
This study was aimed to develop a game called Scrabble Kimia as a learning media in Petroleum topic for senior high school grade XI. This study used the research and development (R and D) type with the 4-D model. This 4-D model has four steps of research, they are define, design, develop, and disseminate. This study was limited only on validity and practicality tests. Data collecting was done by using questionnaires. Validity test used validation questionnaires by four experts, which is two chemistry lectures of the State University of Padang and two chemistry teachers of SMAN 1 Lengayang. Practicality test used practicality questionnaires by two chemistry teachers and 27 students of SMAN 1 Lengayang. Data analyzing used was kappa cohen formula. The result of this study showed that this media has 0,93 validity value with very high category of validity. The result of practicality by chemistry teachers has 0,88 practicality value with very high category of practicality, and practicality by students has 0,70 practicality value with high category of practicality. In conclusion, Scrabble Kimia that has been developed is valid and practice for using as a learning media in petroleum topic for senior high school grade XI.